Sodium bicarbonate ingestion in a fasted state improves 16.1-km cycling time-trial performance - Leach, N. K.; Hilton, N. P.; Tinnion, D.; Dobson, B.; McNaughton, L. R.; Sparks, S. A. (Medicine & Science in Sports & Exercise, 2023)
Purpose The use of sodium bicarbonate (SB) as a preexercise ergogenic aid has been extensively studied in short-duration high-intensity exercise. Very few studies have considered the effects of SB ingestion before prolonged high-intensity exercise. The aim of the present study was to determine the effects of a 0.3 g·kg-1 body mass dose of SB ingested before the start of a 16.1-km cycling time trial in cyclists.